Assessing the survival impact of perioperative opioid consumption in children and adolescents undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Issue 6 (17th April 2017) - Owusu‐Agyemang, Pascal; Hayes‐Jordan, Andrea; Van Meter, Antoinette; Williams, Uduak U.; Zavala, Acsa M.; Kapoor, Ravish; Popovich, Shannon M.; Rebello, Elizabeth; Feng, Lei; Cata, Juan P.
Summary: Background: Several studies in adult patients have suggested an unfavorable association between opioid consumption and cancer progression. Aims: This study investigated the impact of opioid consumption on the survival of children and adolescents undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Methods: A retrospective study of patients <19 years who had undergone cytoreductive surgery with hyperthermic intraperitoneal chemotherapy was performed. Univariate and multivariate Cox proportional hazard analyses were used to identify factors associated with recurrence‐free survival and overall survival. Results: Seventy‐five patients were identified. Median age was 11.6 years (range, 1.8–18.9), and 43% was female. Median perioperative opioid consumption was 18.9 morphine dose equivalents per kilogram (range, 0.6–339.6). There was no statistically significant association between opioid consumption and recurrence‐free survival [hazard ratio, 1.00; 95% confidence interval, (0.99–1.02), P = 0.55] or overall survival [hazard ratio 1.01; 95% confidence interval (0.99–1.03), P = 0.22]. Independent prognostic factors associated with poor survival included incomplete cytoreduction and extra‐abdominal disease. Conclusion: In this retrospective study of children and adolescents who had undergone cytoreductive surgery with hyperthermic intraperitoneal chemotherapy, there was no statistically significant association between opioid consumption and recurrence‐free survival or overall survival. Abstract :